The development of higher education in Africa prospects and challenges - Wiseman, Alexander W., 1968-; Wolhuter, C. C. (Charl C.) (Bingley, U.K. : Emerald, 2013)
The global education revolution of the 20th century resulted in massive developments in education worldwide, but the higher education sector throughout Africa remains surprisingly underdeveloped. Although impressive expansion and reform of higher education in Africa have occurred since 1990, the higher education sector across Africa has been particularly challenged to keep pace with the development of higher education worldwide. This is reflected in comparatively limited research output by African university scholars and researchers and the limited representation of African universities on world institutional rankings. Given both the perceived and real gap in research productivity and scholarly reputation between African higher education and higher education systems in other parts of the world, the question persists whether or not the African higher education sector can produce "world-class" universities.
The incalculable promise of the African continent : higher education rising to the occasion? / Charl C. Wolhuter, Alexander W. Wiseman -- An overview of African higher education and development / Christopher S. Collins -- Trends in internationalization of higher education and implications for research and innovation for development in African universities / Ibrahim Ogachi Oanda -- Cross-border higher education in Africa : collaboration and competition / Jason E. Lane, Kevin Kinser -- "Steering rather than rowing" : internationalism, privatization, and university reform in Tanzania / Ross J. Benbow -- Power of global-local partnerships : an assessment of global, national and local stakeholders of religious, higher education in Sub-Saharan Africa / Grace Karram -- In search of equity and access in higher education in Namibia : challenges and achievements / Kenneth Kamwi Matengu, Gilbert Likando, Bennett Kangumu -- Charting higher education development in Ghana : growth, transformations, and challenges / Francis Atuahene -- Language in higher education transformation : contrasts and similarities between two African universities / Gregory H. Kamwendo -- Knowledge production in the knowledge economy : higher education institutions and the application of innovations in ICT for capacity development in Africa / Chijioke J. Evoh, Christopher Byalusago Mugimu, Hopestone K. Chavula -- Challenges and experiences in doing university collaboration in north-south projects / Zehlia Babaci-Wilhite -- Towards African higher education regionalization and harmonization : functional, organizational and political approaches / Jane Knight -- European education policies and the uniformization of higher education in Europe : some lessons from the Bologna process for education and teacher education in Africa / Konstantinos G. Karras -- Policy spaces and educational development in the Islamic Maghreb region : higher education in Tunisia / Landis G. Fryer , Tavis D. Jules -- Rethinking agency in university development : the case of the association of African universities / Ane Turner Johnson -- Rethinking higher education curriculum in Nigeria to meet global challenges in the 21st century / Martha Nkechinyere Amadi, Perpetua Ememe.
Includes indexes.
Print version record
Keywords: Education -- Philosophy & Social Aspects; Education -- Higher; Higher & further education, tertiary education; Educational strategies & policy; Education, Higher -- Africa